A Study of Geographical Development Based on Agriculture in Hanumangarh District: Exploring the Impact of Agricultural Development on Geographical Transformation in Hanumangarh District (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Hanumangarh district was formed on 12.7.1994 from earlier Ganganagar district as 31st district of Rajasthan state. Seven tehsils of Ganganagar districts of Bikaner division viz. Sangaria, Tibi, Hanumangarh, Pilibanga, Rawatsar, Nohar and Bhadra were included into the newly created district of Hanumangarh. The district headquarter Hanumangarh is situated on the bank of Ghaggar River which is the present form of the last mythological river Saraswati. Ghaggar River, which is called as ‘Nali’ in local dialect divides the district headquarter into two parts. In the north of Ghaggar River, Hanumangarh Town and in the south the habitation of Hanumangarh Junction is situated.Job of agriculture stays imperative in empowering the district to accomplish and keep up nourishment self-sufficiency, particularly, in a poverty-stricken district. Supportable development of agriculture depends essentially on the procedure of horticultural change, which thus is very much associated with movements in cropping patterns. Lazy move in the cropping pattern towards non-sustenance grain crops in the district is because of moderate development of irrigation, low degree of fertilizer utilization, slow technology adoption and low degree of infrastructure.